2020
DOI: 10.3390/brainsci10100666
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Hypothalamic MicroRNAs as Promising Therapeutics for SARS-CoV-2 by Regulating ACE2 and TMPRSS2 Expression: An In Silico Analysis

Abstract: Background: Neuroinvasion of severe acute respiratory syndrome coronavirus (SARS-CoV) is well documented and, given the similarities between this virus and SARS-CoV-2, it seems that the neurological impairment that is associated with coronavirus disease 2019 (COVID-19) is due to SARS-CoV-2 neuroinvasion. Hypothalamic circuits are exposed to the entry of the virus via the olfactory bulb and interact centrally with crucial respiratory nuclei. Hypothalamic microRNAs are considered as potential biomarkers and modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 71 publications
1
35
0
Order By: Relevance
“… Repressed transcription of miR-125a-5p as a result of JARID1B action increases ACE2 protein expression levels. let-7a-5p TMPRSS2 Expression negatively correlated with TMPRSS2 expression Mukhopadhyay and Mussa, 2020 , Nersisyan et al, 2020b . Target the 3’UTR sequence of TMPRSS2 mRNA let-7d-5p TMPRSS2 Expression negatively correlated with TMPRSS2 expression Target the 3’UTR sequence of TMPRSS2 mRNA Mukhopadhyay and Mussa, 2020 , Nersisyan et al, 2020b .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“… Repressed transcription of miR-125a-5p as a result of JARID1B action increases ACE2 protein expression levels. let-7a-5p TMPRSS2 Expression negatively correlated with TMPRSS2 expression Mukhopadhyay and Mussa, 2020 , Nersisyan et al, 2020b . Target the 3’UTR sequence of TMPRSS2 mRNA let-7d-5p TMPRSS2 Expression negatively correlated with TMPRSS2 expression Target the 3’UTR sequence of TMPRSS2 mRNA Mukhopadhyay and Mussa, 2020 , Nersisyan et al, 2020b .…”
Section: Resultsmentioning
confidence: 94%
“… let-7a-5p TMPRSS2 Expression negatively correlated with TMPRSS2 expression Mukhopadhyay and Mussa, 2020 , Nersisyan et al, 2020b . Target the 3’UTR sequence of TMPRSS2 mRNA let-7d-5p TMPRSS2 Expression negatively correlated with TMPRSS2 expression Target the 3’UTR sequence of TMPRSS2 mRNA Mukhopadhyay and Mussa, 2020 , Nersisyan et al, 2020b . miR-922 PI3 GO molecular function: endopeptidase inhibitor activity, peptidase inhibitor activity, endopeptidase regulator activity Taz et al, 2020 , PDCD1 This protein was found upregulated in SARS-CoV-2 infected samples.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, the ACE2 receptor was suppressed by targeting its 3' UTR gene by hsa-miR-23b-5p and hsa-miR-769-5p [35]. 31 miRNAs and 29 miRNAs can downregulate hypothalamic ACE2 and TMPRSS2 gene expression, respectively, suggesting that they might be useful in treating SARS-CoV-2 neuroinvasion, by blocking virus entry [36]. In another study, miR-200 c suppressed ACE2 mRNA and protein expression in rat primary cardiomyocytes and human-induced pluripotent stem cell-derived cardiomyocytes, suggesting a promising strategy to treat SARS-CoV-2 cardiovascular complications [37].…”
Section: Attachment and Entrymentioning
confidence: 99%